2017
DOI: 10.15671/hjbc.2017.172
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aspartame on Acetylcholinesterase Activity in Some of Rat Tissues

Abstract: Ö Z B u çalışmada, sıçanlara intraperional verilen aspartamın, karaciğer, akciğer, böbrek ve beyin dokularında asetilkolinesteraz (AChE) aktivitesindeki değişiklikler araştırıldı. Yapay tatlandırıcı olarak yaygın bir şekilde kullanılan aspartam, erkek Wistar sıçanlara (n= 36) 50, 100 ve 200 mg/kg olarak verildi. Enjeksiyonu takiben 12 ve 24 saat sonra enzim aktivitesindeki değişiklikler kaydedildi. 12 saatteki bütün dozlarda AChE aktiviteleri karaciğer ve böbrekte önemli bir şekilde daha yüksekti. Fakat akciğe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
(41 reference statements)
2
1
0
Order By: Relevance
“…The xenobiotics are converted to more water-soluble (hydrophilic), less toxic and easily excreted from the system. The results of the liver and plasma GST were found to be significantly different at (P < 0.05) compared to the control group for both female and male animals, which was in agreement with Arbind et al (2014) as reported by Polat et al (2017). It was observed that the plant extract reduced the levels of AChE in a dose-dependent manner in male and female Wister rats.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The xenobiotics are converted to more water-soluble (hydrophilic), less toxic and easily excreted from the system. The results of the liver and plasma GST were found to be significantly different at (P < 0.05) compared to the control group for both female and male animals, which was in agreement with Arbind et al (2014) as reported by Polat et al (2017). It was observed that the plant extract reduced the levels of AChE in a dose-dependent manner in male and female Wister rats.…”
Section: Resultssupporting
confidence: 90%
“…These enzymes (AChE and GST), play a crucial role as indicators in the detection of toxicants. The work corroborates the report ofPolat et al (2017) on a decrease in the activities of AChE in animals exposed to organophosphate insecticide, a decrease in AChE activity in the frontal cortex of the rats exposed to metabolites of aspartame and the inhibition of AChE activity in rat hippocampus aspartame metabolites. The results of this study imply that bioactive compounds present in the study plant may cause a reduction in the activities of enzymes involved in the metabolism of foreign substances (pesticides) thereby leading to consequences such as tremor, reduction in the rate of survival and death.…”
supporting
confidence: 90%
“…But the same high values were not observed in the lungs and brain. However, activities in the liver and kidney were similar to the control 24 hours after the administration of 200 mg/kg (20). In a study where the adverse effects on experimental animals were discussed, it was found that 250, 500 and 1000 mg/kg/day aspartame consumption significantly increased the liver enzymes alanine aminotransferase (ALT) and aspartate aminotransferase (AST) (19).…”
Section: Experimental Studies On Aspartamementioning
confidence: 94%